Analysis currency supply and demand from the population of the Republic of Belarus - Rudakovski, Yan S. (Journal of the Belarusian State University. Economics, 2020)
The research presents an analysis of supply and demand of currencies from the population in Belarus. In particular, the supply is mainly formed due to the inflow of remittances. The latter depend on the economic situation in Russia. Demand for foreign currency depends on wages in dollar terms and interest rate parity.